2018
DOI: 10.1002/jcp.27915
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA HOXC13‐AS positively affects cell proliferation and invasion in nasopharyngeal carcinoma via modulating miR‐383‐3p/HMGA2 axis

Abstract: Long noncoding RNAs have been reported to be important regulators in numerous cancers. In this study, we found that HOXC13 antisense RNA (HOXC13‐AS) was highly expressed in head and neck squamous carcinoma (HNSC) tissues in The Cancer Genome Atlas database. Nasopharyngeal carcinoma (NPC) belongs to HNSC. Therefore, we further investigated the potential role of HOXC13‐AS in NPC. Quantitative reverse transcription polymerase chain reaction examination revealed that HOXC13‐AS was markedly upregulated in NPC tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 36 publications
1
31
0
1
Order By: Relevance
“…A recent study reported that HOXC13-AS was obviously upregulated in breast cancers and promoted cell proliferation by regulating the miR-497-5p/PTEN axis (Li et al, 2019b). HOXC13-AS positively affects cell proliferation and invasion by modulating the miR-383-3p/HMGA2 axis in NPC (Gao et al, 2019). In our study, there was an obvious increase in LINC00958 and HOXC13-AS expression at the mRNA level between HNSCC and adjacent tissues.…”
Section: Discussionsupporting
confidence: 62%
“…A recent study reported that HOXC13-AS was obviously upregulated in breast cancers and promoted cell proliferation by regulating the miR-497-5p/PTEN axis (Li et al, 2019b). HOXC13-AS positively affects cell proliferation and invasion by modulating the miR-383-3p/HMGA2 axis in NPC (Gao et al, 2019). In our study, there was an obvious increase in LINC00958 and HOXC13-AS expression at the mRNA level between HNSCC and adjacent tissues.…”
Section: Discussionsupporting
confidence: 62%
“…Tatangelo et al (38) reported a significant upregulation in the expression of HOXC13 and HOTAIR in right (proximal) side of CRCs tissues. Overexpression of HOXC13-AS has been reported in nasopharyngeal carcinoma (39). To the best of our knowledge, the present study is the first to evaluate the expression of HOXC13-AS in CRC, and the results showed that there was no significant difference in the expression of HOXC13-AS between normal and cancer tissues.…”
Section: Discussionmentioning
confidence: 46%
“…Accordingly, HAND2-AS1 has been recently shown to inhibit cancer cell proliferation, migration, and invasion in esophagus squamous cell carcinoma and colorectal cancer by sponging oncogenic microRNA, including miR-21 33,34 . HOXC13-AS (up-regulated in poor prognosis iCCA from our lncRNA signature) has been shown to positively affects cell proliferation and invasion in nasopharyngeal carcinoma by sponging miR-383-3p 35 . CDKN2B-AS1, also known as antisense non-coding RNA in the INK4 locus (ANRIL), was identified as a prognostic biomarker, not only in iCCA, but also in hepatocellular, kidney and uterine corpus carcinomas.…”
mentioning
confidence: 94%